2017
DOI: 10.1245/s10434-017-5829-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Computed Tomography: Measured Parameters of Body Composition in Primary Operable Gastrointestinal Cancers

Abstract: BackgroundPrevious reports suggest that body composition parameters can be used to predict outcomes for patients with gastrointestinal (GI) cancers. However, evidence for an association with long-term survival is conflicting, with much of the data derived from patients with advanced disease. This study examined the effect of body composition on survival in primary operable GI cancer.MethodsPatients with resectable adenocarcinoma of the GI tract (esophagus, stomach, colon, rectum) between 2006 and 2014 were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 33 publications
5
60
2
10
Order By: Relevance
“…Some of the previous studies, all recruiting patients from Asian populations, suggested an increased risk of death among patients with sarcopenia and GC with hazard ratio (HR) of 1.6‐2.7 . Detailed data from Western countries are not available, but in a mixed population of patients with various gastrointestinal malignancies, including 65 GCs, SMI of sarcopenia did not influence survival . However, results from our well‐defined clinical cohort demonstrated that sarcopenia was an independent prognostic factor (HR, 1.94; 95% CI, 1.08‐3.48) irrespective of tumor stage and radicality of resection.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Some of the previous studies, all recruiting patients from Asian populations, suggested an increased risk of death among patients with sarcopenia and GC with hazard ratio (HR) of 1.6‐2.7 . Detailed data from Western countries are not available, but in a mixed population of patients with various gastrointestinal malignancies, including 65 GCs, SMI of sarcopenia did not influence survival . However, results from our well‐defined clinical cohort demonstrated that sarcopenia was an independent prognostic factor (HR, 1.94; 95% CI, 1.08‐3.48) irrespective of tumor stage and radicality of resection.…”
Section: Discussionmentioning
confidence: 63%
“…29,33,37 Detailed data from Western countries are not available, but in a mixed population of patients with various gastrointestinal malignancies, including 65 GCs, SMI of sarcopenia did not influence survival. 12 However, results from our well-defined clinical cohort demonstrated that sarcopenia was an independent prognostic factor (HR, 1.94; 95% CI, 1.08-3.48) irrespective of tumor stage and radicality of resection. Nevertheless, the exact mechanism possibly linking sarcopenia with impaired survival is still unclear.…”
Section: Sarcopenia and Long-term Survivalmentioning
confidence: 67%
See 2 more Smart Citations
“…13 The importance of the systemic inflammatory response as a unifying mechanism for weight loss and loss of lean tissue in patients with cancer is increasingly recognized. 3,14,15 Therefore, it is of interest that SMI and SMD have been repeatedly reported to be inversely associated with measures of the systemic inflammatory response, such as the neutrophil lymphocyte ratio (NLR) and modified Glasgow prognostic score (mGPS), [16][17][18][19][20][21][22] that are recognized to have prognostic value in their own right. 23,24 However, this relationship is not clear.…”
Section: Introductionmentioning
confidence: 99%